The compressive strength and impact of seawater on foamed concrete with untreated timber husk as additive for a floating mechanism / Mizan Adillia Ahmad Fuad, Zalena Abdul Aziz and Nooriati Taib - Ahmad Fuad, Mizan Adillia; Abdul Aziz, Zalena; Taib, Nooriati (2022)
Floating architecture has become a solution to land scarcity and rising sea levels. Studies have been done on lightweight concrete as an appropriate building material for structures on water. Hence, this paper focuses on untreated timber husk as another element mixed with lightweight concrete (foamed concrete) to create diversity and sustainability for building materials. This study is made to look at different percentages of untreated timber husk as additive in foamed concrete as a floating architecture building material while looking at its durability and buoyancy towards seawater by an experimental with numerical studies on the specification and properties of lightweight. The quantitative method's finding shows that it is achievable to design a floating timber-foamed concrete, where samples offer a range of densities between 437.5 – 993.3 kg/m³. Compressive strength is tested for each model during different curing periods, and the highest reading is produced by TH05 which is 2.27 MPa and 0.89 MPa; after been submerged in seawater. The buoyancy of samples is also analysed using seawater over time, and the surface of each concrete shows the most reaction on TH15, and rate of impact from seawater towards the strength was best at TH10 with only 0.25 MPa difference. Further analysis of the impact of seawater shall be observed to see the effects of seawater on the density and strength of timber-foamed concrete over time.